2016
DOI: 10.3748/wjg.v22.i39.8820
|View full text |Cite
|
Sign up to set email alerts
|

22-gauge core vs 22-gauge aspiration needle for endoscopic ultrasound-guided sampling of abdominal masses

Abstract: AIMTo compare the aspiration needle (AN) and core biopsy needle (PC) in endoscopic ultrasound-guided fine needle aspiration (EUS-FNA) of abdominal masses.METHODSConsecutive patients referred for EUS-FNA were included in this prospective single-center trial. Each patient underwent a puncture of the lesion with both standard 22-gauge (G) AN (Echo Tip Ultra; Cook Medical, Bloomington, Indiana, United States) and the novel 22G PC (EchoTip ProCore; Cook Medical, Bloomington, Indiana, United States) in a randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 42 publications
0
35
0
Order By: Relevance
“…To overcome these limitations associated with the aspiration needle, a new biopsy needle with reverse‐bevel technology (ProCore; Cook Endoscopy, Winston‐Salem, NC) was developed. This new core biopsy needle device was designed to obtain cytological aspirates and histological core samples simultaneously and has shown promising results for pancreatic tumors and lymph nodes . However, data on the feasibility and efficacy of EUS‐guided fine‐needle biopsy (EUS‐FNB) with this new needle device in patients with gastric SET remain limited .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome these limitations associated with the aspiration needle, a new biopsy needle with reverse‐bevel technology (ProCore; Cook Endoscopy, Winston‐Salem, NC) was developed. This new core biopsy needle device was designed to obtain cytological aspirates and histological core samples simultaneously and has shown promising results for pancreatic tumors and lymph nodes . However, data on the feasibility and efficacy of EUS‐guided fine‐needle biopsy (EUS‐FNB) with this new needle device in patients with gastric SET remain limited .…”
Section: Introductionmentioning
confidence: 99%
“…This new core biopsy needle device was designed to obtain cytological aspirates and histological core samples simultaneously and has shown promising results for pancreatic tumors and lymph nodes. [5][6][7][8][9][10][11] However, data on the feasibility and efficacy of EUS-guided fine-needle biopsy (EUS-FNB) with this new needle device in patients with gastric SET remain limited. [12][13][14][15] We therefore performed a prospective, single-center, randomized controlled trial to compare the diagnostic yield of EUS-FNA with that of EUS-FNB in patients with gastric SET.…”
Section: Introductionmentioning
confidence: 99%
“…The PC20 and PC22 employ a core trap system, which contributes to increased tissue acquisition and preservation of the histological structure [22]. A core trap can reportedly ensure effective cellularity for diagnosis [20,23]. Acquiring tissue specimens with minimal structural damage increases the histopathological quality of the samples.…”
Section: Discussionmentioning
confidence: 99%
“…This core trap system is designed to improve the acquisition of core biopsy specimens. Sterlacci et al [20] reported that EUS tissue sampling using a 22-gauge (22G) needle with a core trap increased the accuracy of pathological diagnosis for abdominal masses compared with using a 22G aspiration needle. EchoTip ProCore® needles of various diameters are currently available.…”
Section: Introductionmentioning
confidence: 99%
“…After the needle had successfully entered the target puncture mass, its stylet was withdrawn and suction was applied using a 10-ml syringe. Finally, the needle was removed from the mass after suction had been released [33,34]. The number of passes depended on the endosonographer's estimation of the yielded material and ease of the operation (for this study, at least two passes were performed).…”
Section: Methodsmentioning
confidence: 99%